PENERAPAN SISTEM PENILAIAN KINERJA ; DAMPAKNYA TERHADAP KEPUASAN DAN STRES KERJA KARYAWAN - Dwipayana, Arif Devi; Supartha, Wayah Gede; Sintaasih, Desak Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The objective of this research is to analyze the effect of the performance evaluation system on job satisfaction and work stress. Samples amounted to 86 employees of the 635 population employees PT. Aerofood Indonesia branch Aerofood ACS Denpasar. Data analyzed using “Structural Equation Modelling (SEM) based on covariance partial least square (PLS)”. The results showed the performance appraisal system significant and positive effect on job satisfaction. Performance appraisal system significant and negative related to work stress. Job satisfaction significant and negative effect on work stress. Implications of this research is running all the indicators and procedures of performance evaluation system by increasing work satisfaction thus getting lower employees stress.   Keywords : performance appraisal, work satisfaction, work stress.